Cost-Effectiveness of Collaborative Care for Depression in HIV Clinics. (1st December 2015) - Painter, Jacob T.; Fortney, John C.; Gifford, Allen L.; Rimland, David; Monson, Thomas; Rodriguez-Barradas, Maria C.; Pyne, Jeffrey M.
Abstract : Objective: To examine the cost-effectiveness of the HIV Translating Initiatives for Depression Into Effective Solutions (HITIDES) intervention. Design: Randomized controlled effectiveness and implementation trial comparing depression collaborative care with enhanced usual care. Setting: Three Veterans Health Administration HIV clinics in the Southern United States. Subjects: Two hundred forty-nine HIV-infected patients completed the baseline interview; 123 were randomized to the intervention and 126 to usual care. Intervention: HITIDES consisted of an offsite HIV depression care team that delivered up to 12 months of collaborative care. The intervention used a stepped-care model for depression treatment, and specific recommendations were based on the Texas Medication Algorithm Project and the VA/Department of Defense Depression Treatment Guidelines. Main Outcome Measures: Quality-adjusted life years (QALYs) were calculated using the 12-Item Short Form Health Survey, the Quality of Well Being Scale, and by converting depression-free days to QALYs. The base case analysis used outpatient, pharmacy, patient, and intervention costs. Cost-effectiveness was calculated using incremental cost-effectiveness ratios (ICERs) and net health benefit. ICER distributions were generated using nonparametric bootstrap with replacement sampling. Results: The HITIDES intervention was more effective and cost saving compared with usual care in 78% of bootstrapped samples. The intervention net health benefit was positive and therefore deemed cost-effective using an ICER threshold of $50, 000/QALY. Conclusions: In HIV clinic settings, this intervention was more effective and cost saving compared with usual care. Implementation of offsite depression collaborative care programs in specialty care settings may be a strategy that not only improves outcomes for patients but also maximizes the efficient use of limited health care resources.